Effect of core strengthening and dynamic hip mobility exercises on non-specific low back pain in female police officers - Desai, Anushka; Srinivasan , Anandh (Indian Journal of Community Health, 2024)
Background: Non-specific lower back pain (NSLBP) is prevalent among female police officers, influenced by genetic factors, aging, and occupational risks such as heavy lifting. This study evaluates a 6-week program combining core strengthening and hip mobility exercises to alleviate NSLBP. Objective: To assess the effectiveness of core strengthening and dynamic hip mobility exercises in reducing NSLBP among female officers. Methods and Material: The study involved 40 female officers aged 25-55 with NSLBP lasting at least 6 weeks using simple random sampling technique. Participants were randomly assigned to Group A (control) or Group B (experimental). Group B underwent a 6-week core strengthening and hip mobility exercise regimen, with pain intensity (NPRS) and low back disability (ODI) measured before and after. Results: Group B exhibited significantly lower pain intensity (3.5 ± 1.147 vs 7.3 ± 0.9234) and reduced low back disability (13.6 ± 2.909 vs 28.65 ± 2.207) compared to Group A. Conclusions: The study revealed that among female officers with NSLBP, core strengthening and hip mobility exercises proved more effective than traditional exercises in alleviating pain and reducing low back instability